Seismic Behavior and Vulnerability of Masonry Dwellings in Eastern Türkiye: A Comprehensive Analysis - Resat Oyguc (Applied Sciences)
From 1940 to the present, Turkish seismic standards for masonry building have gradually evolved, culminating in the performance-based TBEC (2018). Unregulated tenant expansions and informal construction, especially in rural areas, continue to be a significant cause of seismic risk despite developments in ring beam design, mortar categorization, and capacity-based criteria. This paper critically examines the structural flaws caused by such expansions in partly built unreinforced masonry homes, focusing in particular on areas of moderate-to-high seismicity. The research shows that occupant changes often ignore necessary seismic protections by means of post-earthquake field observations, comparative code analysis, and recorded failure patterns. Among them are wall slenderness ratios, ring beam continuity, and masonry unit and mortar quality checks. Common ensuing failures include corner disintegration, roof–wall separation, and diagonal shear cracking. Relying on qualitative analysis of reoccurring damage mechanisms seen during field investigations, the results come from post-disaster evaluations of 2568 masonry dwellings after the 2023 Kahramanmaraş earthquakes. This paper emphasizes a continual gap between seismic rules and informal building practice and contends that without official acknowledgment of owner-built changes, code efficacy stays constrained. These results are also of worldwide importance for earthquake-prone areas struggling to control informal or self-built buildings.